2002
DOI: 10.1128/jb.184.18.5058-5066.2002
|View full text |Cite
|
Sign up to set email alerts
|

Temperature- and H-NS-Dependent Regulation of a Plasmid-Encoded Virulence Operon Expressing Escherichia coli Hemolysin

Abstract: Proteins H-NS and Hha form a nucleoprotein complex that modulates expression of the thermoregulated hly operon of Escherichia coli. We have been able to identify two H-NS binding sites in the hly regulatory region. One of them partially overlaps the promoter region (site II), and the other is located about 2 kbp upstream (site I). In contrast, Hha protein did not show any preference for specific sequences. In vitro, temperature influences the affinity of H-NS for a DNA fragment containing both binding sites an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
123
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(129 citation statements)
references
References 44 publications
6
123
0
Order By: Relevance
“…Negative modulation of hilA is also accomplished by global modulators such as Hha (Fahlen et al, 2001) and H-NS (Olekhnovich & Kadner, 2006;Schechter et al, 2003). Both belong to the superfamily of the nucleoid-associated proteins (Dorman, 2004;Madrid et al, 2007) and have been shown to interact to modulate gene expression (Ellison & Miller, 2006;Madrid et al, 2002;Nieto et al, 1991Nieto et al, , 2002. The nucleoid-associated protein H-NS is a well-characterized example of a modulator that influences gene expression in response to environmental stimuli such as osmolarity, pH and temperature (Hulton et al, 1990;Hommais et al, 2001;Ono et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Negative modulation of hilA is also accomplished by global modulators such as Hha (Fahlen et al, 2001) and H-NS (Olekhnovich & Kadner, 2006;Schechter et al, 2003). Both belong to the superfamily of the nucleoid-associated proteins (Dorman, 2004;Madrid et al, 2007) and have been shown to interact to modulate gene expression (Ellison & Miller, 2006;Madrid et al, 2002;Nieto et al, 1991Nieto et al, , 2002. The nucleoid-associated protein H-NS is a well-characterized example of a modulator that influences gene expression in response to environmental stimuli such as osmolarity, pH and temperature (Hulton et al, 1990;Hommais et al, 2001;Ono et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These low mobility complexes seem not to be very efficient in repressing hly expression. Specific repression seems to be related to the formation of DNA loops in which H-NS oligomers bridge two sites separated by a region of intrinsic curvature [22]. Stiff rods of DNA covered by H-NS oligomers could be less mobile than DNA loops due to the different shape and also to the smaller number of H-NS molecules per DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The 2.8 kbp DNA fragment used, corresponding to the regulatory region of the hly operon of E. coli, was obtained by PCR amplification from plasmid pHly152 [22].…”
Section: Band Shift Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these Western blot data taken together with the hemolytic phenotype of 34.7 noted on SRBC agar and in tube assays indicate that hemolysin production is deregulated in 34.7. Similarly, H-NS in complex with Hha, a protein that belongs to a relatively new family of modulators, controls the expression of the thermoregulated a-hemolysin operon encoded by uropathogenic Escherichia coli [25].…”
Section: Phenotypic Analysis and Complementation Of Mutant 347 With mentioning
confidence: 99%